2000
DOI: 10.1002/1529-0131(200004)43:4<801::aid-anr10>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 induction of collagenase 3 (matrix metalloproteinase 13) gene expression in chondrocytes requires p38, c-jun N-terminal kinase, and nuclear factor κB: Differential regulation of collagenase 1 and collagenase 3

Abstract: Proteolytic degradation of articular cartilage is a hallmark of osteoarthritic (OA) joint destruction. Articular cartilage contains chondrocytes embedded in an avascular matrix composed primarily of type II collagen (CII) fibrils and the proteoglycan, aggrecan. Collagen fibrils provide tensile strength and serve as a lattice to anchor water-laden proteoglycans, which deform while absorbing impact loads (1). OA chondrocytes and the adjacent synovial tissue secrete the inflammatory cytokine interleukin-1␤ (IL-1␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

41
428
2
7

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 603 publications
(478 citation statements)
references
References 49 publications
41
428
2
7
Order By: Relevance
“…2654 BAU ET AL With respect to modulation by IL-1␤ in vitro, 2 classes of proteases were detectable. The first showed strong up-regulation by IL-1␤ and included MMP-1 (4,(46)(47)(48), MMP-3 (3), and MMP-13 (4,5,48), genes known to contain promoter elements that are responsive to IL-1 stimulation. ADAM-TS4 was also induced, which was observed in some studies (49) but was missed in others (45).…”
Section: Discussionmentioning
confidence: 99%
“…2654 BAU ET AL With respect to modulation by IL-1␤ in vitro, 2 classes of proteases were detectable. The first showed strong up-regulation by IL-1␤ and included MMP-1 (4,(46)(47)(48), MMP-3 (3), and MMP-13 (4,5,48), genes known to contain promoter elements that are responsive to IL-1 stimulation. ADAM-TS4 was also induced, which was observed in some studies (49) but was missed in others (45).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies have also shown that retinoid-related signals strongly enhance the induction of MMP-13 in chondrocytic cells through the action of RAR-RXR heterodimers (45). In addition, reduced expression of MMP-13 is observed in cytokine-stimulated cells when NF-B is maintained in the cytoplasm by constitutive levels of I B (46). Thus, it can be speculated that MMP-13 is also induced by HA 6 through these transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…One milliliter of serum-free medium from each well of a 6-well plate containing the SW-1353 cells was precipitated with 500 l of cold 10% trichloroacetic acid, and the proteins were pelleted as described previously (20). The pellets were washed and resuspended in Laemmli sample buffer (Sigma, St. Louis, MO), separated by electrophoresis (Bio-Rad, Hercules, CA), and transferred to an Immobilon-P polyvinylidene difluoride membrane (Millipore, Bedford, MA).…”
Section: Methodsmentioning
confidence: 99%
“…LG100268 (LG268) and the SW-1353 human chondrosarcoma cell line, a model system for proinflammatory cytokine induction of MMP production by chondrocytes (20)(21)(22). Our data showed that LG268 selectively inhibited the proinflammatory cytokine-induced upregulation of MMP-1 and MMP-13 by decreasing the transcription rate of these genes.…”
mentioning
confidence: 87%
See 1 more Smart Citation